Ownership, empowerment and employees’ participation on budgetary slack: An investigation of Malaysian public sector / Cheok Mui Yee - Cheok , Mui Yee (2017)
The New Public Management (NPM) sought to promote market-oriented administration and result-based management of public sector organisations in Malaysia. However, the National Audit Department found that public sector organisations experienced glitches in expenditure management; particularly in the availability of resources and budget estimation, which were highlighted in the Auditor’s General Report, 2011. This concern highlights the existence of budgetary slack in Malaysian public sector organisations. It appears that employees through their participation in budget-setting, create budgetary slack in the participative budgeting system, which permeates throughout the organisations. The budgetary slack creation concern has encouraged numerous researchers to examine the determinants of budgetary slack. However, they have focused their examination efforts at an organisational level in private sector organisations, therefore, a new research is required to investigate the determinants of budgetary slack at an individual level in public sector organisations. The main objective of this study is to empirically examine how budgetary slack is influenced by employees’ psychological ownership and empowerment (i.e., structural and psychological), and participation in budget making. The research was designed and performed in five phases to collect data from individual participants (i.e., budget makers). In the first phase, the researcher performed (expert) interviews with professional and management accountants to examine the determinants of budgetary slack in the research model. Later, a pilot test was performed to validate the original budgetary slack (OBS) instrument attributed to Onsi (1973). In the third phase, the researcher developed a new budgetary slack instrument, after acknowledging the deficiency of OBS instrument. In phase four, a pilot test was conducted to validate the determinants of budgetary slack. Lastly, a field study was performed to collect data using a questionnaire survey; which was then used for empirical analysis in the final stage. This study analysed the data using component-based Structural Equation Modelling (PLS-SEM). After evaluating the requirements of measurement and structural models, the study developed an empirical model, about the effect of psychological ownership, empowerment (structural and psychological) and participation on budgetary slack. The results highlight that empowerment (structural and psychological) was an important determinant of the creation of budgetary slack among budget makers in public sector organisations in Malaysia. Besides, employees’ participation was a predictor of budget makers’ behaviour in participative budgeting in public sector organisations. This study also highlighted another two interesting findings. The first one is that employees’ psychological state of ownership did not result in the creation of budgetary slack among budget makers in public sector organisations, when structural empowerment was taken into consideration. The other one is that formal ownership was not present in public sector organisations. In conclusion, this study examined the determinants of budgetary slack among budget makers in public sector organisations beyond the traditional perspective. It highlights the importance of recognising empowerment as a key determinant of slack creation in budgeting. Hence, public sector organisations might have to centralise the budgeting practice within their hierarchical structure to avoid the creation of budgetary slack.